2000
DOI: 10.1081/dmr-100100575
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation Capacity of Neonatal Mice in Relation to the Neonatal Mouse Tumorigenicity Bioassay

Abstract: The neonatal mouse tumorigenicity bioassay is a well-developed animal model that has recently been recommended as an alternative tumorigenicity bioassay by the International Conference on Harmonization (ICH) for Technical Requirements for the Registration of Pharmaceuticals for Human Use. There are sufficient data to conclude that this animal model is highly sensitive to genotoxic chemical carcinogens that exert their tumorigenicity through mechanisms involving the formation of covalently bound exogenous DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Lee (2000) demonstrated that DEN treatment in the preweaning period induced only basophilic cell-type tumors and never eosinophilic and clear cell types in the B6C3F1 strain. Others (Klaunig et al 1987(Klaunig et al , 1988Fu et al 2000) have shown an inhibitory response of lesion growth and formation in preneoplastic foci by tumorpromoting compounds such as phenobarbital in 15-day-old DEN-initiated mice. These results suggested that the initiation process (DEN treatment) must occur in the postweaning period for the initiation promotion with classical tumor promoters to occur in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee (2000) demonstrated that DEN treatment in the preweaning period induced only basophilic cell-type tumors and never eosinophilic and clear cell types in the B6C3F1 strain. Others (Klaunig et al 1987(Klaunig et al , 1988Fu et al 2000) have shown an inhibitory response of lesion growth and formation in preneoplastic foci by tumorpromoting compounds such as phenobarbital in 15-day-old DEN-initiated mice. These results suggested that the initiation process (DEN treatment) must occur in the postweaning period for the initiation promotion with classical tumor promoters to occur in mice.…”
Section: Discussionmentioning
confidence: 99%
“…DEN itself induces hepatic neoplastic and preneoplastic lesion in mice (Goldfarb et al 1983). To induce hepatic tumors by DEN, infant mice are often used as the developing liver is susceptible especially to genotoxic chemical carcinogens (Vesselinovitch et al 1984;Fu et al 2000). The distinct initiation-promotion steps of the multistage hepatocarcinogenesis model are well recognized.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of additional evidence [Fu et al, 2000] clearly establishes the sensitivity of the neonatal mouse to carcinogenesis induced by genotoxic agents. This evidence has particularly relevant implications for assessing potential carcinogenic risks posed by AZT, since exposure through the HAART regimen takes place perinatally, the period of maximal sensitivity of mice to other genotoxic carcinogens.…”
Section: Abstract: Hiv; Azt; Genotoxicitymentioning
confidence: 99%
“…Electrophilic neurotoxins, including acrylamide, may cause protein structure and function changes by oxidation and this may lead to pathway failure and finally nerve cell damage. Therefore such chemicals at low doses and long-term exposure might be a cause of neurodegenerative diseases such as Alzheimer's disease (12,35,53,54) . The studies on neurotoxic effects of acrylamide and glycidamide are summarised in Table 1 (29,35,55 -57) .…”
Section: Neurotoxic Effects Of Acrylamidementioning
confidence: 99%
“…Glycidamide was found to induce N-7-(2-carbamoyl-2-hydroxy-ethyl)guanine Fu et al (2000) (35) Neonatal mouse tumorigenicity bioassay Glycidamide showed 5-to 7-fold higher DNA adduct levels than when treated with acrylamide, indicating lower levels of CYP450 enzymes in immature tissues Gamboa de Costa et al (41) Micronucleus assay on hens' eggs Acrylamide increased micronucleus frequencies Recio et al (2010) (42) Micronucleus/comet assays on rats and mice Acrylamide was found to induce micronucleated reticulocytes in rats Mei et al (2010) (43) Micronucleus and Hprt assays on rats Neither acrylamide nor glycidamide increased the frequency of micronucleated reticulocytes. In contrast, both compounds produced small (approximately 2-to 3-fold above background) but significant increases in lymphocyte Hprt mutant frequency Neurotoxic effects of acrylamide …”
Section: Reproductive and Developmental Toxicity Of Acrylamidementioning
confidence: 99%